Masstige strategies on social media: The influence on sentiments and attitude toward the brand - Bilro, R.G.; Loureiro, S. M. C.; Dos Santos, J. F. (International Journal of Consumer Studies, 2022)
This paper explores whether mass prestige (masstige) campaigns, providing luxury and exclusivity for the masses, influence sentiments and attitude toward the brand among fashion customers and followers on social media, namely Facebook and Instagram. Two brands are selected within the fashion sector: a luxury fashion brand—Gucci—and a mass-market fashion brand—H&M. This research grounds its methodology on a netnography, collecting a total of 336,504 comments. The comments are examined through sentiment analysis based on a text-mining technique. The findings reveal that fashion brands can promote masstige strategies, sustaining attitude toward the brand, widening their range of offers, and taking the chance on these types of campaigns without negatively affecting customers’ and followers’ sentiments on social media platforms. The use of comments to measure these topics empirically is a novelty of this research.